A Nose Towards the Future: Reimagining Deep Brain Stimulation with Deep Focus - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Neuromodulation is undergoing a paradigm shift, moving beyond the binary of invasive versus non-invasive interventions. This report describes two emerging techniques, DeepFocus and Vagus Nerve Stimulation (VNS) that exemplify this evolution. DeepFocus, utilizes nasal anatomical access to deliver focal electrical stimulation to deep brain regions implicated in mood and reward, such as Brodmann area 25 and the medial orbitofrontal cortex. Paired with the DeepROAST computational platform for precise current modelling, DeepFocus demonstrates strong, targeted electric fields in cadaveric studies without requiring craniotomy. In contrast, VNS, an approved therapy for epilepsy, depression, and stroke rehabilitation, modulates brain function indirectly via afferent vagal pathways and shows durable clinical benefit, particularly when paired with task-specific rehabilitation. While DeepFocus remains in the preclinical stage, it offers unprecedented deep brain targeting with minimal invasiveness. VNS, though requiring implantation, is already integrated into standard care. These techniques are not mutually exclusive but represent complementary strategies in a growing toolkit of personalized neuromodulation that promise to transform treatment for neurological and psychiatric disorders.
Keywords: Deep brain stimulation; Neuromodulation; DeepFocus; Vagus nerve stimulation; Computational modelling